Iowa Birdline update, February 28, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email for the Iowa Birdline update for February 28, 1994. Highlights include a Greater Prairie-Chicken and a Varied Thrush. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed